About the arterial blood vessels pelvic opossum's (Didelphis albiventris) behaviour - Carvalho, R. G.; Souza, W. M.; Prada, I. L S; Souza, N. T M (My University, 1990)
The work consists of the study of 20 opossums (Didelphis albiventris); 7 females and 13 males, adults, natives of Jaboticabal county proceeding to a canulation and injection of the arterial system with neoprene latex-650 in the aorta artery (full-blooded). Right away the preparations were fixed by a 10% formaldehyde aqueous solution and afterwards dissected and formed a scheme. The analysis of the pieces showed that in the opossum, the end of the aorta always divides in the common iliac artery, right and left sides, both originating the external and internal iliac artery, on the right and left sides. The medium sacral artery results, medianly, from the aorta division's angle in 2 common iliac arteries in 8 cases (40% - 6 males and 2 females); this vessel comes from the left common iliac artery in 7 animals (35% - 5 males and 2 females) or comes from the right common iliac artery, in 5 preparations (25% - 3 females and 2 males). The deep iliac circumflex artery is born by the common iliac artery from the right side in 10 preparations (50% - 6 males and 4 females), can appear as well, concomitantly with the external and internal iliac artery, from the right side in 9 pieces (45% - 6 males and 3 females) and further from the right this vessels can emerge from the external iliac artery, in 1 case only (5% - 1 male).
Keywords: artery; iliac artery; mammal; nonhuman; opossum; pelvis; Animal; Aorta; Arteries; Female; Male; Opossums; Pelvis